2016
DOI: 10.31436/imjm.v15i2.387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aromatherapy on Anxiety and Vital Signs of Myocardial Infarction Patients in Intensive Care Units

Abstract: Introduction: Patients with myocardial infarction (MI) who were admitted to CCU experience anxiety. Anxiety increases the risk of ischemia and worsens the prognosis of MI. The aim of this study was to determine the effects of inhaling lavender oil on anxiety levels and vital signs in MI patients. Methods: A randomized controlled trial was performed. Sixty patients with MI were randomly assigned to the intervention and control group. The intervention group inhaled the essential oil of Lavender for three days (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Non-pharmacological treatments include complementary and alternative medicine (CAM), aromatherapy, massage therapy, etc. [ 10 ]. which can be used alone or in combination with other methods [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-pharmacological treatments include complementary and alternative medicine (CAM), aromatherapy, massage therapy, etc. [ 10 ]. which can be used alone or in combination with other methods [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most popular aromatherapy oils today is a lavender essential oil containing linalool, which can be used through inhalation or massage on the skin. Previous research results showed the positive effects of lavender oil used in aromatherapy, among others: helps relax tense nerves and muscles (Sayorwan et al, 2012), improves sleep quality (Cho et al, 2013;Karadag et al, 2017), lowering heart rate and body temperature (Jalalodini et al, 2016;Salamati et al, 2017;Sayorwan et al, 2012), lowering blood pressure (Jalalodini et al, 2016;N et al, 2016;Salamati et al, 2017;Sayorwan et al, 2012), reducing anxiety (Cho et al, 2013;Donelli et al, 2019;Karadag et al, 2017;Karan, 2019). Sayorwan et al (2012) found that lavender aromatherapy can increase alpha brain waves (8-13 Hz) associated with decreased stress and theta waves (4-8Hz), thereby improving sleep quality.…”
Section: Introductionmentioning
confidence: 99%